ANALYSE DES DIFFICULTES RENCONTREES PAR LES ELEVES DE 6ème ANNEE DES HUMANITES SCIENTIFIQUES SUR LA RESOLUTION DES EQUATIONS DU TROISIEME DEGRE DANS ₵ (Cas de Quelques Ecoles Non Conventionnées de la ville de Kisangani : 2019 – 2020) - André, IGBOLO PAMBULA (IJRDO - Journal of Social Science and Humanities Research, 2021)
In the context of active pedagogy research, learning Mathematics is imperative.Some quadratic equations solved in the set R whose discriminant is negative have not found solutions. This is why a new set of complex numbers has been born, made up of the real and imaginary parts.It was during our teaching career in Mathematics that we noticed that some Scientist finalist students had difficulty solving a 3rd degree equation in ₵, which difficulties constituted a real educational problem. The major cause of these difficulties is the lack of mastery of the method of binomial divisors of the independent term to determine Z0, the first root of the given equation, Horner’s rule to find the quotient Q (Z) = az2 + bz + c, the computation of the discriminant of Q (Z) = 0 and the search for the square roots of this discriminant to finally find the full roots of the starting equation.Our study is conducted on a sample of 120 students where only 21 students (17.5%) performed well when solving these equations against 99 students (82.5%) who experienced serious difficulties. The coefficients were the main variables in our research.